Clinical Efficacy of Vibrating Mesh and Jet Nebulizers With Different Interfaces in Pediatric Subjects With Asthma. - Moody, Gerald B.; Luckett, Peter M.; Shockley, Courtney M.; Huang, Rong; Ari, Arzu (Respiratory Care, 2020)
BACKGROUND: Nebulizers are commonly used in emergency departments to deliver bronchodilators to children with asthma exacerbations. However, no clinical study comparing a vibrating mesh nebulizer with a jet nebulizer is available in this patient population. The purpose of this study was to compare the clinical efficacy of a vibrating mesh nebulizer to a jet nebulizer combined with a mouthpiece or mask in children with asthma exacerbations admitted to the emergency department. METHODS: We conducted a single-blinded randomized clinical trial of 217 children (2-18 y old) with a moderate to severe asthma exacerbation in the emergency department. Assessment of severity was defined by our acute asthma score, adapted from the Pediatric Asthma Score. Subjects were randomized to receive bronchodilator treatment via vibrating mesh nebulizer (n = 108) or jet nebulizer (n = 109) and were treated until they achieved a mild asthma score and were discharged or until a decision to admit was made. All subjects were treated per our acute asthma clinical pathway algorithm for the emergency department with modifications to allow for blinding, assessment of treatment, and data collection. Outcome variables included hospital admission rate, number of treatments, and time to mild asthma score. RESULTS: There was a significant difference in baseline asthma score between subjects treated with the vibrating mesh nebulizer and those treated with the jet nebulizer (P = .042), but no other significant differences in demographics existed between groups. To adjust for effect of baseline asthma score, a multiple logistic regression model was used to model admission. The vibrating mesh nebulizer group had a lower probability of being admitted to the hospital (P = .062), and they required significantly fewer treatments (P < .001) and less time to reach a mild asthma score (P = .004) than those in the jet nebulizer group. In subjects with a mask interface, the vibrating mesh nebulizer significantly reduced the probability of admission (P = .032). CONCLUSIONS: Subjects treated with a vibrating mesh nebulizer required significantly fewer treatments and less time to achieve a mild asthma score. In subjects with a mask interface, the vibrating mesh nebulizer significantly reduced the probability of admission compared to jet nebulizer.